2014
DOI: 10.1016/j.bbamcr.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Everything old is new again: An update on current research on the Cpx envelope stress response

Abstract: The Cpx envelope stress response (ESR) has been linked to proteins that are integrated into and secreted across the inner membrane for several decades. Initial studies of the cpx locus linked it to alterations in the protein content of both the inner and outer membrane, together with changes in proton motive driven transport and conjugation. Since the mid 1990s, the predominant view of the Cpx envelope stress response has been that it serves to detect and respond to secreted, misfolded proteins in the periplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
217
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(223 citation statements)
references
References 128 publications
6
217
0
Order By: Relevance
“…We and others have shown that copper can induce genes of the CpxR/CpxA regulon (21)(22)(23). This, along with the pH-dependence in cueP expression, another CpxR/CpxA-activating condition (24), prompted us to investigate the contribution of this regulatory system to cueP expression. Deletion of the response regulator gene cpxR and/or the sensor kinase coding gene cpxA abrogated the metal induction of cueP at pH 7.0 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that copper can induce genes of the CpxR/CpxA regulon (21)(22)(23). This, along with the pH-dependence in cueP expression, another CpxR/CpxA-activating condition (24), prompted us to investigate the contribution of this regulatory system to cueP expression. Deletion of the response regulator gene cpxR and/or the sensor kinase coding gene cpxA abrogated the metal induction of cueP at pH 7.0 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4,8,12 The small periplasmic protein CpxP, encoded immediately upstream of the cpxRA operon, inhibits the system, perhaps by forming an inhibitory complex with CpxA, although this remains in question. 11 This negative regulation might be relieved when CpxP is degraded, perhaps in association with misfolded proteins. However, CpxP is not required for activation of the Cpx response by any known inducing signals, including misfolded proteins.…”
Section: The Cpx Esrmentioning
confidence: 99%
“…11,12 Its core components are the IM histidine kinase CpxA and the cytoplasmic response regulator CpxR. Cpx inducing conditions include exposure to alkaline pH, overproduction and accumulation of pilus subunits in the periplasm, mutations that impact periplasmic protein folding, and exposure to environmental conditions that alter the composition of the bacterial cell envelope.…”
Section: Introduction To Gram-negative Esrsmentioning
confidence: 99%
“…Although several stress response systems are known to sense and respond to damaged/misfolded membrane proteins (13)(14)(15), there is a paucity of knowledge regarding systems that sense and ameliorate damage to the cell wall. Exceptions are TCS [e.g., WalRK and VraSR (16,17)] found in several Gram-positive genera that respond to exposure to various cell-wall-acting antibiotics by activating regulons that mediate specialized cell wall synthesis/turnover functions.…”
mentioning
confidence: 99%